The Utilization Lizardfish As Base Material for Fish Jelly Processing With Arrrowroot Starch Addition - Putut Har Riyadi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2006)
Processing of lizardfish (Saurida tumbil) for fish jelly product one of alternative product diversification that expect to be an acceptable product to the society. In Japan, Lizardfish has become generally used as raw material for producing fish jelly product. Meanwhile, arrow roots starch is considered to be the best choice for alternative substitute material of wheat in large scale. This research was aimed to observed the proper heating temperature and concentration of arrowroot starch and effect of the period of storage on quality of the fish jelly product. The research using laboratoriy experimental method. The result showed that different concept of arrowroot starch gave significant effect on the gel strength, elasticity, WHC, whiteness, expcep for pH, folding test (p<0,05). The concentration of arrowroot starch (10%) gave highest gel strength on optime heat temperature 90 oC. The lenght of storage had significant effect to the quality of fish jelly product. The longer the storage time to be held, lower the value gel strength, elasticity, WHC, whiteness and folding test. Key words : Lizardfish, fishjelly product, arrowroot starch